2013
DOI: 10.1039/c3cc46791k
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt catalysts for the conversion of CO2 to light hydrocarbons at atmospheric pressure

Abstract: A series of cobalt heterogeneous catalysts have been developed that are effective for the conversion of CO2 to hydrocarbons. The effect of the promoter and loadings have been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…Here, it is important to note that there is no significant effect of pressure on the conversion of CO 2 below 270°C. This fact indicates that CO 2 ‐FT reaction will yield desirable results with bit lower chain HCs at low pressure and low temperature, which is supported by various experimental studies conducted at atmospheric pressure . However, increase in temperature up to 477°C is favorable for long chain HCs synthesis at higher pressure .…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Here, it is important to note that there is no significant effect of pressure on the conversion of CO 2 below 270°C. This fact indicates that CO 2 ‐FT reaction will yield desirable results with bit lower chain HCs at low pressure and low temperature, which is supported by various experimental studies conducted at atmospheric pressure . However, increase in temperature up to 477°C is favorable for long chain HCs synthesis at higher pressure .…”
Section: Resultsmentioning
confidence: 69%
“… reported that the long chain HC formation from CO 2 is thermodynamically unfavorable. However, their conclusion is not same as discovered from the recent experimental studies . Yao et al .…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…13 Most of the work in the area is focused on the use of Al2O3 supports, generally used in industrial Fischer Tropsch processes. 14 However, some studies have demonstrated that other inorganic oxide supports such as TiO2 can outperform Al2O3 in the Fischer Tropsch process using CO/H2 feeds.…”
Section: 10mentioning
confidence: 99%
“…[1,2] Generally,cobalt-based catalysts give ahigh selectivity to methane, most likely due to their poor water-gas shift activity. [17] While recent studies have indicated that promoted cobalt systemsc an be effectively used for the formation of hydrocarbonsf rom CO 2 , [18] iron'si nherent water-gas shift activity has resulted in it being the main focus for the formation of C 2 + hydrocarbons. [1,10] The authors have recently shown that while an iron-silica catalysth as relatively low activity with selectivityp rimarily to methane, the addition of promoters can shift selectivity towards lower (C 2 -C 4 )o lefins over 40 %.…”
Section: Introductionmentioning
confidence: 99%